Incidence of physical injuries in a rural community in Sri Lanka: Results of the first community survey in Sri Lanka - Lamawansa M; Piyathilake A (Wolters Kluwer Medknow Publications, 2008)
Background: Injuries account for approximately 11% of all hospital admissions in Sri Lanka. However, no published data are available with regard to the community incidence of injuries in Sri Lanka. Objectives: To determine the community incidence of major intentional and unintentional physical injuries in a rural community in Sri Lanka. Materials and Methods: A rural community consisting of 225 families with 1029 inhabitants was studied. Data on major injuries for a period of one year were collected retrospectively. Results: There were 85 major injuries in the community during the year of study. This gives a major injury incidence of 82.6 per 1000 person years. This is three times the incidence based on hospital-derived data. Animal bites being the most common cause of injury was noted in 2.3% of the population followed by falls in 1.6%, contact with objects in 1.5%, cut injuries in 1% and road trauma in 1%. Conclusions: This study shows a higher incidence of major physical injuries (both intentional and unintentional) in the community than figures derived from hospital data. The prevention of injuries in a community such as the one studied here should be aimed at animal bites, falls, contacts with objects, cut injuries and road trauma.